2002
DOI: 10.1071/wr01104
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of plague rodents and dasyurids as prey of barn owls in central Australia

Abstract: We examined the diet of the barn owl in three bioregions of arid Northern Territory; two in upland areas, the other on the Barkly Tableland. Owls from the MacDonnell and Petermann Ranges fed predominantly on rodents. At both sites, Mus musculus was the dominant prey both in terms of frequency and prey units, with Pseudomys hermannsburgensis an important secondary item. Notomys alexis was an important secondary item in the MacDonnell Ranges. These results support previous research in highlighting the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Heywood and pavey (2002) found that barn owls are capable of switching to other prey when rodent populations decline, while Morton and Martin (1979) found that the barn owl became uncommon (due to dispersal or starvation) after a drop in abundance of their main prey species, and that they did not switch to an alternative prey.…”
Section: Discussionmentioning
confidence: 97%
“…Heywood and pavey (2002) found that barn owls are capable of switching to other prey when rodent populations decline, while Morton and Martin (1979) found that the barn owl became uncommon (due to dispersal or starvation) after a drop in abundance of their main prey species, and that they did not switch to an alternative prey.…”
Section: Discussionmentioning
confidence: 97%
“…Kulcsszavak: reprodukciós kimenet, táplálékfogyasztás, alternatív zsákmány, gradáció 1 University of Pécs, Faculty of Sciences, Institute of Biology, Department of Ecology, 7624 Pécs, Ifjúság utca 6., Hungary 2 Baranya County Group of BirdLife Hungary, 7632 Pécs, Siklósi út 94., Hungary BirdLife Hungary, 1121 Budapest, Költő utca 21., Hungary * corresponding author, e-mail: hgypte@gamma.ttk.pte.hu prey were reported by studies particularly in arid environments, where food intake results supported that the Common Barn-owl is a rather selective opportunistic predator (Heywood & Pavey 2002, Tores et al 2005, McDowell & Medlin 2009, Romano et al 2020.…”
Section: Introductionmentioning
confidence: 73%
“…Avenant (2005) showed that frequencies of barn owl prey in South Africa closely matched the frequencies of prey available in the surrounding small animal community. In addition, studies have shown that Australian barn owls, which are typically nomadic and follow rodent irruptions, can have considerable dietary flexibility and are capable of consuming a diet consisting primarily of marsupials (Heywood and Pavey, 2002) or even reptiles (McDowell and Medlin, 2009). Therefore, the differences of species presence and frequency observed between INPA and TRHA are likely to represent differences in the proximal living communities at the time(s) of predation.…”
Section: Discussionmentioning
confidence: 99%